O silêncio do espaço: a cartografia social no ensino da cartografia para alunos (as) surdos (as) - Nunes, Katiana Lourenço (2023)
The aim of this research is to discuss the theoretical basis of school cartography for deaf students from a social cartography perspective. Despite the debate around inclusive education for deaf people, the epistemological and pedagogical assumptions of cartography teaching in schools are alien to the specificities (cognitive, cultural, symbolic, social, existential and political) of these subjects. Social Cartography, as a critical approach to traditional conceptions of space and territory, is emerging today as a concept with enormous pedagogical potential, especially for deaf people. Based on a bibliographical study of School Cartography, Deafness (LADD, 2013) and Social Cartography, we emphasize that: 1. traditional approaches to School Cartography distance themselves from the cognitive, cultural and symbolic specificities of deaf subjects; 2. in addition to the linguistic aspect, cartography teaching must consider 'Deaf Culture' and the 'way of being-deaf'; 3. Social Cartography starts from a geographical conception that questions the ideological and political character contained in traditional cartographic language and production. We conclude that Social Cartography has an intrinsic epistemological and pedagogical basis that favors inclusion and consideration of deaf students' own ways of thinking, learning, expressing and communicating.